“Necesidad de Reformar la Ley de Minería en cuanto a las Funciones de la Empresa Nacional Minera (ENAMI), por su Ineficiente Acción” - SUÁREZ REINOSO., JOSÉ ANDRÉS (2021)
This research work entitled “Necesidad de Reformar la Ley de Minería en cuanto a las Funciones de la Empresa Nacional Minera (ENAMI), por su Ineficiente Acción”, includes a Conceptual, Doctrinal and Legal Study, in addition to Comparative Legislation and the application of the different methods and techniques, with which it was possible to verify the Objectives and contrast the Hypothesis. The problem raised in the investigative work is based on the non-fulfillment of the aims and objectives for which the National Mining Company was created, because according to the results obtained, this body has not fulfilled the established purposes such as administering mining resources and therefore it is not generating profits; In addition, it has been verified in the field study that this mining company does not have the experience or lack of professionalism and the necessary resources, therefore it has made so many failures in its administration, in addition, since instead of generating economic revenues it has produced expenses; To which is added the fact that the tasks carried out by ENAMI are the same that it can perfectly fulfill and that are assigned, by law, to the INIGEMM Geological Mining and Metallurgical Research Institute; today called the Geological and Energy Research Institute. To which is added the fact that strategic mining contracts will always be made by the Sectorial Ministry. It should be noted that, through the study of the Doctrinary Framework, as well as in Comparative Law, it can be determined that, in countries such as Colombia, Peru and Chile, the opposite occurs, since in 3 their laws establish that the state companies in charge of the mining activity, are formed mostly by private capital, and these are the main producers of the vast majority of non-renewable natural resources, such as mining projects, paying for expenses and increasing investors. 5 Due to the aforementioned, a reform to the Mining Law is necessary and urgent, with respect to the National Mining Company due to its inefficient action and the breach of its social purposes, a proposal that has also been supported by legal professionals, experts in mining, whom I surveyed and interviewed.